The fictional translator in Anglophone literatures - Curran, Beverley (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The use of English is commonly taken to be one of the distinctive features of globalization and Anglophone cultural hegemony. Is the appearance of the fictional translator in English writing an indication of deliberate resistance to “the global parochialism of Anglophone monoglossia” (Cronin 2003: 60)? Or are these imagined translators weak echoes of the same ‘questions of colonialism and cultural hegemony’ raised by Third World postcolonial plurilingual writers, writing in the language of the ex-colonizer? Are these characters the authors’ wistful attempts to construct a bilingual conscious-ness denied them through assimilation? These are the overarching questions that this paper will attempt to answer by looking at the fictional translator as a character and linguistic presence in writing in English through an examination of Michael Ondaatje ’s The English Patient (1992), David Malouf’s Remembering Babylon (1993), and Jonathan Safran Foer’s Everything is Illuminated (2002). The presence of the fictional translator in Canadian, Australian, and American writing in English suggests that the agent of discursive migration is operative even within regions of stubborn Anglophone monoglossia. If translators are agents of change, how do they operate in Anglophone writing in late modernity? And why is their presence so often awkward, unreliable, and even painful? I will argue that the fictional translator registers anglophone angst in spite of the lan guage ’s powerful global influence and publishing power.